TÜRKİYE'DEKİ TERÖR VE TERÖRLE MÜCADELE YÖNTEMLERİ ÜZERİNE SOSYOLOJİK BİR İNCELEME - BAYBAŞ, ŞÜKRÜ (Fırat Üniveristesi, 2007)
Although human?s life is defined as the greatest asset primarily in religion books andthen national and international agreements, all documents where rights and freedoms arestated, violence and aggression against human haven?t been surceased. Any reason does notjustify killing human who is the most respectful creature of the nature. In the 21st century welive, no matter for what reason, thought or aim, besides terrorism that means all the violenceand deterrence acts against human, if we are faced with the reality of war that ignoreshuman?s life, mankind should overview all thought system that he has developed so far.It is an inevitable reality that the people who have share the same world and defenceopposite opinions are in conflict and fight. So at national and international level theseconflicts should be removed and state governed by the rule of law where primarily socialjustice, social security and besides equality and fair sharing, human rights, democracy andfreedoms are under guarantee in whole societies and where law is taken as a base should beactualised. The terrorist acts in our country negatively affect our development. Our countryhas got great material and emotional loss in terrorism battle. Just like in other countries thepreliminary condition to fight against terror is to perceive world and country?s realityaccurately as soon as legal arrangements come up and to transfer this accurate to the laws inaccordance with law?s basic mentality.Key Words: Terror, Terrorism, Terror Groups in Turkey, Terrorist Profile, Fightingwith Terrorism.
A sociological analyze on terror in Turkey and struggle methods on terrorism
Keywords: Sosyoloji